Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.7150/ijbs.17053
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 3 is required for osteogenic differentiation through maintenance of PGC-1ɑ-SOD2-mediated regulation of mitochondrial function

Abstract: Osteogenic differentiation is crucial for the maintenance of bone homeostasis. Sirtuin 3 (SIRT3), a member of sirtuins family, functions as a critical deacetylase that regulates many key proteins. In the current study, we aimed to clarify the role of SIRT3 in osteogenic differentiation and the possible mechanisms, using mouse pre-osteoblastic MC3T3-E1 cells. Expression of SIRT3 was substantially increased in differentiated MC3T3-E1 cells. Knock down of SIRT3 significantly decreased alkaline phosphatase (ALP) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 34 publications
1
53
0
Order By: Relevance
“…In agreement with our findings, a recent in vitro study revealed that SIRT was significantly increased after the therapy with CURC under hyperglycemic conditions . Interestingly, Ding et al, using mouse pre‐osteoblastic MC3T3‐E1 cells, showed that SIRT is required for osteogenic differentiation, supporting the relevant biological role of this marker in conditions involving bone tissue breakdown, as revealed in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our findings, a recent in vitro study revealed that SIRT was significantly increased after the therapy with CURC under hyperglycemic conditions . Interestingly, Ding et al, using mouse pre‐osteoblastic MC3T3‐E1 cells, showed that SIRT is required for osteogenic differentiation, supporting the relevant biological role of this marker in conditions involving bone tissue breakdown, as revealed in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the expression of Errα was significantly decreased in the IDH2KO HFD mice, and because ERRα is a major DNAbinding partner for PGC-1α, its reduction would lead to an even further decrease in the expression of key mitochondrial genes. These genes include Sirt3 and Sod2, which are both activated by the concerted action of ERRα and PGC-1α [24][25][26] . In fact, prior studies have suggested that Sirt3 is important for limiting oxidative damage 27 through regulating IDH2 deacetylation 28,29 .…”
mentioning
confidence: 99%
“…This further improved oxygen consumption rate and the NAD + /NADH ratio through compensatory mechanism which increased mitochondrial mass and bioenergetics acting via PGC1α-SIRT3-UCP2 axis [21]. The relationship between SIRT3 and PGC1α has already been well discussed in previous studies [22][23][24].…”
Section: Importance Of Sirt3 As a Mitochondrial Switchmentioning
confidence: 67%